2012
DOI: 10.1007/s10995-012-0985-z
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Depression Postpartum and 12 years Later-Associations to Child Mental Health at 12 years of Age

Abstract: Children of depressed mothers have been shown to express behaviour problems to a greater extent than children of non-depressed mothers. The purpose of this study was to examine the persistence of depressive symptoms in mothers and to evaluate the relative importance of symptoms of postpartum depression (PPD) and concurrent maternal symptoms of depression, on child behaviour at age 12. A birth cohort of 1,707 children and their mothers was followed from 3 months after birth to 12 years after birth. Self-reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 39 publications
7
65
0
1
Order By: Relevance
“…The results presented here indicate that main consequences for the child in growing up in a family with a parent with mental illness are reversal of the parenting role in the family, emotional and behavioural problems (insecurity, anxiety, not attending school, antisocial behaviour), stigma of being part of a 'mental health case' and lack of parental attention and engagement with the child. Similar findings have been reported in the WPA Guidelines (Brockington et al, 2013), and in several previous studies (Agnafors et al 2013;Cooklin 2009Cooklin , 2013Gladstone et al 2006;Manning & Gregoire 2006;Maybery et al 2005;Reupert et al 2012b;Somers 2007;Trondsen 2012;Weizmal et al 2011). These studies have also highlighted parental emotional unavailability, the disturbed behaviour of children and reversal of the roles in family with a parent with mental illness.…”
Section: Discussionsupporting
confidence: 90%
“…The results presented here indicate that main consequences for the child in growing up in a family with a parent with mental illness are reversal of the parenting role in the family, emotional and behavioural problems (insecurity, anxiety, not attending school, antisocial behaviour), stigma of being part of a 'mental health case' and lack of parental attention and engagement with the child. Similar findings have been reported in the WPA Guidelines (Brockington et al, 2013), and in several previous studies (Agnafors et al 2013;Cooklin 2009Cooklin , 2013Gladstone et al 2006;Manning & Gregoire 2006;Maybery et al 2005;Reupert et al 2012b;Somers 2007;Trondsen 2012;Weizmal et al 2011). These studies have also highlighted parental emotional unavailability, the disturbed behaviour of children and reversal of the roles in family with a parent with mental illness.…”
Section: Discussionsupporting
confidence: 90%
“…What this finding may also suggest is that other women who did not report mental health impairment in pregnancy went on to experience mental health impairment in the years following their baby's birth. Overall, this observed increase in the proportion of women with mental health impairment at 21 years was not unexpected, as other findings have reported similar increases in the proportion of women with depression, over studies of four years (Woolhouse et al, 2015) and 12 years (Agnafors et al, 2013). While, having poor mental health in pregnancy proved to be one of the strongest predictors of maternal poor mental health over time, other contributing factors reported in this thesis' findings, such as women's socio-demographic and lifestyle characteristics and other factors, no doubt influence the mental health of this latter group of women.…”
Section: Proportions and Patterns Of Women's Mental Health Impairmentsupporting
confidence: 82%
“…Further evidence has found that exposure to maternal depression was associated with internalizing and externalizing behaviours in school-aged children (Barker et al, 2012, Fihrer et al, 2009). While another study found concurrent maternal symptoms of depression and anxiety was associated with behavioural problems in children (Agnafors et al, 2013).…”
Section: Offspring Behaviours and Women's Mental Health Over Timementioning
confidence: 95%
See 1 more Smart Citation
“…Behavioural problems are also present in the pre-teen years (Agnafors, Sydsjo, Dekeyser, & Svedin, 2013); however, this effect does not seem to be caused by MPPD, but rather by prolonged and recurring maternal depression after the postpartum period (Agnafors et al, 2013).…”
mentioning
confidence: 99%